River of smoke - Ghosh, Amitav (John Murray, 2011)
Amid a cyclone in the Bay of Bengal, three vessels, and the diverse occupants within, converge on Canton's Fanqui-Town, or Foreign Enclave, which is a powder keg awaiting a spark to ignite the Opium Wars